2021
DOI: 10.1128/jcm.00213-21
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Changes to the Clinical and Laboratory Standards Institute Performance Standards for Antimicrobial Susceptibility Testing, M100, 31st Edition

Abstract: The Clinical and Laboratory Standards Institute (CLSI) Subcommittee on Antimicrobial Susceptibility Testing (AST) develops and publishes standards and guidelines for AST methods and results interpretation, in an annual update to the Performance Standards for Antimicrobial Susceptibility Testing (M100). This mini-review will discuss changes to M100 for the 31 st Edition, including new and revised breakpoints and testing recommendations. New MIC and disk diffusion breakpoints are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
310
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(318 citation statements)
references
References 31 publications
5
310
0
3
Order By: Relevance
“…In this study, a conservative approach was adopted in assigning resistance to probiotics. For the disc diffusion assay, the quality control data in the manufacturer’s technical guide which followed the performance standards for antimicrobial disk susceptibility tests of the Clinical and Laboratory Standards Institute (CLSI) [ 73 ], suggested that inhibition zones with diameters less than three times the diameters of the antibiotic discs (<18 mm) were considered resistant for most antibiotics when tested on representative Gram positive ( Staphylococcus aureus ATCC 259230) and Gram negative ( Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853) bacteria but, we assigned resistance only if the inhibition zones were less than two times the diameter of the antibiotic discs (<12 mm). Likewise, for the broth microdilution assays, resistance was only assigned if the MIC values exceeded the thresholds of all Lactobacillus spp.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a conservative approach was adopted in assigning resistance to probiotics. For the disc diffusion assay, the quality control data in the manufacturer’s technical guide which followed the performance standards for antimicrobial disk susceptibility tests of the Clinical and Laboratory Standards Institute (CLSI) [ 73 ], suggested that inhibition zones with diameters less than three times the diameters of the antibiotic discs (<18 mm) were considered resistant for most antibiotics when tested on representative Gram positive ( Staphylococcus aureus ATCC 259230) and Gram negative ( Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853) bacteria but, we assigned resistance only if the inhibition zones were less than two times the diameter of the antibiotic discs (<12 mm). Likewise, for the broth microdilution assays, resistance was only assigned if the MIC values exceeded the thresholds of all Lactobacillus spp.…”
Section: Methodsmentioning
confidence: 99%
“…The isolate was plated on blood and chocolate agar (Autobio, China) plates at 35°C under 5% (v/v) CO 2 before testing ( Humphries et al, 2021 ). Single colonies were selected from the plates.…”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial resistance was analyzed by the disk diffusion method with the following antibiotics (OXOID®): ampicillin (AMP 10µg), fosfomycin (FOS 50µg), cefotaxime (CTX 30µg), amoxicillin/clavulanic acid (AMC 30µg), orfenicol (FFC 30µg), chloramphenicol (C 30µg), gentamicin (CN 10µg), tetracycline (TE 30µg), oxytetracycline (OT 30µg), enro oxacin (ENR 5µg), o oxacin (OFX 5µg), cipro oxacin (CIP 5µg), trimethoprim/Sulfamethoxazole (SXT 25µg), and vancomycin (VA 30µg) as a negative control. The resistance category (sensitive or resistant) was selected based on the Clinical Laboratory Standard Institute guidelines (Humphries et al, 2021).…”
Section: Samples Of Water From the Phytotelmata And Bacterial Antibio...mentioning
confidence: 99%